Evolutionary Theories in Environmental and Resource Economics: Approaches and Applications - Jeroen C.J.M. van den Bergh; John M. Gowdy (Tinbergen Institute, 1998)
Recent advances in evolutionary theory have important implications for environmental economics. A short overview is offered of evolutionarythinking in economics. Subsequently, major concepts and approaches inevolutionary biology and evolutionary economics are presented andcompared. Attention is devoted, among others, to Darwinian selection,punctuated equilibrium, sorting mechanisms, Lamarckian evolution,coevolution and self-organization. Basic features of evolution, such assustained change, irreversible change, unpredictability, qualitativechange and disequilibrium, are examined. It is argued that there are anumber of fundamental differences as well as similarities betweenbiological and economic evolution. Next, some general implications ofevolutionary thinking for environmental economics are outlined. This isfollowed by a more detailed examination of potential uses ofevolutionary theories in specific areas of environmental economics,including sustainability and long run development theories, technologyand environment, ecosystem management and resilience, spatial evolutionand environmental processes, and design of environmental policy.
Keywords: 330; bounded rationality; coevolution; disequilibrium; ecosystems; irreversibility; macroevolution; punctuated equilibrium; sorting; sustainable development; technical change; Umweltökonomik; Ressourcenökonomik; Evolutionsökonomik; Theorie